More patient-centered care, better healthcare: the association between patient-centered care and healthcare outcomes in inpatients - Yu, Chenhao; Xian, Yun; Jing, Tiantian; Bai, Mayangzong; Li, Xueyuan; Li, Jiahui; Liang, Huigang; Yu, Guangjun; Zhang, Zhiruo (Frontiers in Public Health, 2023)
Objective: To explore the association between patient-centered care (PCC) and inpatient healthcare outcome, including self-reported physical and mental health status, subjective necessity of hospitalization and physician-induced demand behaviors.A cross-sectional survey was conducted to assess patient-centered care among inpatients in comprehensive hospitals through QR codes after discharge from September to December 2021 and had 5222 respondents in Jiayuguan, Gansu. The questionnaire included a translated 6-item version of the PCC questionnaire, physician-induced behaviors, and patients' sociodemographic including gender, household registration, age, income, etc. Logistic regression analyses were conducted to assess whether PCC promoted self-reported health, the subjective necessity of hospitalization, and decreased physician-induced demandThe cross-sectional survey with a total of 5222 participants was implemented via QR codes in Jiayuguan, Gansu, from September to December 2021. Participants rated their patient-centered care experience via the 6-item translated Patient-centered care questionnaire, who were inpatients in the comprehensive hospitals in Jiayuguan. The multiple logistic This is a provisional file, not the final typeset article regression was implemented to identify the association. The interactions between PCC and household registration were implemented to assess the difference effect between adequate and inadequate healthcare resources.Results: Patient-centered carePCC promoted patient's self-reported physical (OR = 4.154, p < .001) and mental health (OR = 5.642, p < .001), and subjective necessity of hospitalization (OR = 6.160, p < .001). Meanwhile, patient-centered carePCC reduced physician-induced demand in advising to buy medicines outside (OR = 0.415, p < .001), paying at the outpatient clinic (OR =0.349, p < .001), issuing unnecessary or repeated prescriptions and medical tests (OR = 0.320, p < .001), and requiring discharge and readmitting (OR = 0.389, p < .001).By improving health outcomes for inpatients and reducing the risk of physicianinduced demand, PCC can benefit both patients and health insurance systems. Therefore, PCC should be implemented in healthcare settings.Patient-centered care may promote the healthcare outcome for inpatients and reduce physician-induced demand leading an effective expense in healthcare. Patient-centered care should be adopted for the well-being of patients and the sustainability of healthcare insurance.